Multiple Benefits of Improving Energy Efficiency - Arti Sawant (European Scientific Journal, ESJ, 2017)
The Intergovernmental Panel on Climate Change (IPCC) report states that buildings account 32 percent of the energy use and 19 per cent of the global emissions out of which almost a third can be attributed to the cooling sector. The aim of this paper is to establish the energy efficiency benefits and discuss health benefits from energy efficiency improvements in the emerging economies such as India. Air conditioners are important in targeting the improvement of energy efficiency policies and are the low-hanging fruit of climate policy in India because of its size and rapidly increasing market due to the aspirations of people in the country to improve their standard of living. Montreal Protocol’s latest Amendment, that limits the use of a supergreenhouse gas Hydrofluorocarbons (HFCs) will provide an impetus to the energy efficiency innovations, and has historically catalyzed energy efficiency improvements of up to 35 per cent. Projected growth in power demand for cooling could have a crippling effect on India’s fiscal status and prospects for economic growth to the extent it becomes necessary to further increase fossil fuel imports to maintain pace with high demand for electricity in the cooling sector. Modest energy efficiency improvements saves India billions of US dollars annually, several scores of Gigawatts (GW) of electricity, improved health outcomes in terms of reduced mortality and respiratory diseases and also indirect social impacts from improved health. Thus this paper sheds light on these benefits and establishing a clear unmistakable link between these energy efficiency improvements and health.